2018
DOI: 10.1007/s12038-018-9729-6
|View full text |Cite
|
Sign up to set email alerts
|

Triacylglycerol: nourishing molecule in endurance of Mycobacterium tuberculosis

Abstract: The ability of Mycobacterium tuberculosis (M. tuberculosis) to accumulate lipid-rich molecules as an energy source obtained from host cell debris remains interesting. Additionally, the potential of M. tuberculosis to survive under different stress conditions leading to its dormant state in pathogenesis remains elusive. The exact mechanism by which these lipid bodies generated in M. tuberculosis infection and utilized by bacilli inside infected macrophage for its survival is still not understood. In this, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Approximately 15%–30% of patients with pulmonary TB during pregnancy exhibit hematogenous dissemination and suffer from miliary TB ( Sobhy et al., 2017 ). It has been reported that the reasons for this phenomenon are associated with immune dysregulation ( Mor and Cardenas, 2010 ), increased vascular permeability ( Mali and Meena, 2018 ), or elevated blood lipid levels ( Miele et al., 2020 ) during pregnancy, while miliary TB in pregnancy after IVF-ET is rare and the incidence has not been estimated. Our results reinforced previous findings that women during pregnancy after IVF-ET were more prone to miliary TB ( Ye et al., 2019 ; Gai et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 15%–30% of patients with pulmonary TB during pregnancy exhibit hematogenous dissemination and suffer from miliary TB ( Sobhy et al., 2017 ). It has been reported that the reasons for this phenomenon are associated with immune dysregulation ( Mor and Cardenas, 2010 ), increased vascular permeability ( Mali and Meena, 2018 ), or elevated blood lipid levels ( Miele et al., 2020 ) during pregnancy, while miliary TB in pregnancy after IVF-ET is rare and the incidence has not been estimated. Our results reinforced previous findings that women during pregnancy after IVF-ET were more prone to miliary TB ( Ye et al., 2019 ; Gai et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…After establishing a focus of infection in the lung, bacilli can disseminate via the hematogenous to the most vascular organs, such as brain meningeal involvement, which was evident postmortem in 54% of cases of miliary TB ( Mali and Meena, 2018 ). In our study, 14 out of 75 cases (18.7%) were complicated with TB meningitis and/or encephalitis.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we did not examine the influence of pyruvate and acetate, or any other potential carbon sources for that matter, on ACD/SCD cell division pattern. Further, mycobacteria are known to have adapted to lipids (mostly triacylglycerol) as an evolutionarily important nutrient source enabling their lifestyle vis-à-vis living habitat [ 77 ]. Above all, the present study on the response of Msm , in terms of change in the proportions of the cells dividing by ACD:SCD and the genes involved therein, to yield higher proportion of more stress tolerant NCs and lower proportion of stress susceptible SCs, would enable further investigations on how mycobacteria would change their cell division strategy to maintain a high proportion of stress tolerant NCs in response to the nutrient status.…”
Section: Discussionmentioning
confidence: 99%
“…The major and best known lipid storage molecules in ILIs are triacylglycerides (TAGs), although phosphate-rich or wax esters are also present [ 16 , 17 ]. Specifically, TAGs are important in host-pathogen interactions [ 18 ] as well as in therapeutic applications of mycobacteria [ 19 ]. In this sense, although TAGs seem to be nonreactogenic, they can modify the triggered immune response via a masking phenomenon [ 20 ], becoming key compounds for immunomodulatory therapies.…”
Section: Introductionmentioning
confidence: 99%